Malaysia Economic Monitor, June 2021 : Weathering the Surge - World Bank (World Bank, Washington, DC, 2021)
In recent months, there has been a steep increase in the number of daily new cases and, more disturbingly, in the number of deaths. While it took almost one year for Malaysia to record its first 100,000 cases, the increase in the number of new cases between April to May 2021 alone amounted to more than 100,000. Similarly, while it took about one year for cumulative deaths to reach 500, the cumulative number of deaths in the first two weeks of June alone was more than 500. Even more worryingly, the number of brought-in dead (BID) cases also rose sharply; in May 2021, BID cases accounted for nearly one-third of total deaths. The severity of the current wave has raised concerns regarding the overall capacity of the health system. With the number of new cases and death rates continuing to climb at a rapid rate, the health system has been operating at close to its maximum capacity, with most intensive care units (ICUs) running at nearly 100 percent capacity. At the same time, key containment measures, including mass testing and contact tracing, have not been fully or effectively implemented. In addition, the rollout of the country’s vaccination program is being affected by delayed vaccine supply and high vaccine hesitancy, although there are some signs that the pace has picked up recently. To curb the spread of the pandemic and to ease the burden on the health system, the government has reimposed the movement control order (MCO). Initially, the terms of the MCO allowed for most economic sectors to continue to operate. However, with the number of cases remaining high and with no signs of abatement, the government subsequently announced a full lockdown, with only key essential services allowed to operate. The Ministry of Health has indicated that it may take between 3-4 months to flatten the curve of the pandemic.